11(v+1)-3v=2(4v+3)-13

Simple and best practice solution for 11(v+1)-3v=2(4v+3)-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(v+1)-3v=2(4v+3)-13 equation:


Simplifying
11(v + 1) + -3v = 2(4v + 3) + -13

Reorder the terms:
11(1 + v) + -3v = 2(4v + 3) + -13
(1 * 11 + v * 11) + -3v = 2(4v + 3) + -13
(11 + 11v) + -3v = 2(4v + 3) + -13

Combine like terms: 11v + -3v = 8v
11 + 8v = 2(4v + 3) + -13

Reorder the terms:
11 + 8v = 2(3 + 4v) + -13
11 + 8v = (3 * 2 + 4v * 2) + -13
11 + 8v = (6 + 8v) + -13

Reorder the terms:
11 + 8v = 6 + -13 + 8v

Combine like terms: 6 + -13 = -7
11 + 8v = -7 + 8v

Add '-8v' to each side of the equation.
11 + 8v + -8v = -7 + 8v + -8v

Combine like terms: 8v + -8v = 0
11 + 0 = -7 + 8v + -8v
11 = -7 + 8v + -8v

Combine like terms: 8v + -8v = 0
11 = -7 + 0
11 = -7

Solving
11 = -7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 36g+6=2g(6g+9) | | (7x-25)=(5x+19) | | G=(5/4)(p-91) | | 7-5(2y-1)=3y+2 | | 12y+6=62y+1 | | x=-(-w+6) | | 4x^2+2x-3x^2+8x=0 | | -1x-5=3x+27-10 | | x-(2xy-(2x-2(x+y))-2xy)= | | .55x+.05(6-x)=.10(-37) | | 1200=-300x+2400 | | .6x-1.4=3.3x+1.5 | | 1/2=1/8d | | 2x((y+3x)-2y)= | | T(x)=-300x+2400 | | 2.00x+10.00=6 | | 15a+31=61 | | x^2+2xy-7xy+4y^2=0 | | .50x+.35(70)=29.5 | | 28=x(9-4x) | | l=3(135)-60 | | .4x+9.1=7.3 | | -4a^2b+7+10a^2b=0 | | 3a+(b-(a+2b))= | | S^2=2+2 | | m/3.1415=7.3 | | 15=4w/v | | 100=3.14(x)+3(x) | | 8x^3-7x^3+16x^3=0 | | 2(x-2y)(2x-y)= | | 2(x-8)-2(8)=-3x | | 550=25x |

Equations solver categories